Enhancing Mastery of Basic Football Dribbling Skills among Upper Primary School Students through Augmented Reality-Based Interactive Learning Media - Hasibuan, Ahmad Riady; Sari, Suci Perwita; Sari, Indah Purnama (EDUCATION JOURNAL OF INDONESIA, 2025)
This study aims to improve students’ learning outcomes in the basic football dribbling technique through the implementation of augmented reality (AR) as an interactive learning aid. An experimental method was employed, using pre-tests and post-tests to measure students’ learning gains. The analysis revealed a significant improvement in student performance following the use of AR technology. The average post-test score (69.32) was notably higher than the pre-test score (65.13), with the difference indicating that AR implementation effectively enhanced students’ understanding and skills in dribbling. Homogeneity and normality tests confirmed that the data were normally distributed and homogeneous, thus supporting the validity of the study. Moreover, AR media was shown to foster student motivation and enhance learning interactivity, making it a compelling alternative to increase students’ interest and academic performance, particularly in physical education. Overall, AR technology not only improved learning outcomes but also fostered a more engaging and interactive classroom environment, thereby holding potential to elevate educational quality at the primary level.